KOLABORASI KOMPETENSI GURU PAK DENGAN KETELADANAN HIDUP ORANG TUA UNTUK MEWUJUDKAN KUALITAS PENDIDIKAN ANAK - Pranada Pane; Tony Suhartono; Intan Suriyanti (JURNAL IMPARTA, 2023)
The term collaboration is a form of cooperation carried out between individuals to achieve a common goal to get good results and of course in collaborating between individuals there must be involvement with one another, complementing each other, the point is that there is a process of helping each other in it. The existence of competent teachers and parents who are good role models, if placed in the context of collaboration, will make a good contribution and can also bring the expected results. Teachers and parents are learning resources for students who provide education according to their respective duties and vocations.            Competent teachers are a must in themselves because their duties are to educate, guide and teach while parents to be role models especially for their children is an obligation in nurturing, caring for and not being an obstacle in the growth and development of their children. The child's growth phase is an important and decisive phase, where in this phase the child will move from one phase to another, for this reason, guidance, direction and guidance from the educators, namely teachers and parents are very much needed. The role of teachers and parents is very influential, namely through the competence of teachers and the example given by parents it will give something new because their education will have a big influence on their future.